Nivel de satisfacción y calidad de cuidado de enfermería del paciente postoperado del servicio de cirugía del Hospital Belén de Trujillo - Huamaní Chávez, Sheyla (2016)
This research was conducted in order to determine the relationship between the level of satisfaction and quality of nursing care of postoperative patient service Surgery "A and B" of "Bethlehem Hospital of Trujillo" descriptive, correlational, during the months of May to September 2015, in the Bethlehem Hospital of Trujillo. The sample consisted of 40 adult users post operated Surgery service for data collection 2 instruments were used: Satisfaction Level Rating and Quality of Care Nursing Patient postoperative. The data obtained were tabulated and presented in graphs and statistical tables single and double entry. The analysis of the relationship between the variables of study, a Chi-squared value p = 0.000 is seen to be highly significant, so no relationship between the quality of nursing care and the level of satisfaction. Reached the following conclusions 67.5% of patients have a poor level of satisfaction, and 32.5% a level of good satisfaction, 62.5% of patients show that the quality of care deficient nursing, 22.5% regularly and 15.0% good and 57.5% of patients report that the quality of nursing care is poor and the poor level of satisfaction, 15.0% of patients report that their quality of nursing care is regular and level of satisfaction is good , and 12.5% of patients report that their quality of nursing care is good and your satisfaction is good, there is a relationship between the two variables, highly significant between satisfaction and quality of nursing care of postoperative patient, significance was found when applying statistical chi-square test p = o.oo p <0.05.